Reforming the Public Financial Management System for Better Performance Budgeting in Ivory Coast - Kanyamuna, Vincent; Kone, Yacouba Dit Zonon (Advances in Social Sciences Research Journal, 2022)
Reforming the public finance management system has always been one of the areas which retain more attention when country leaders and development partners want to create a good environment to facilitate poverty alleviation. This study aimed at investigating the way in which Ivory Coast could reform its public financial management (PFM) for a better performance budgeting in order to achieve its goals of poverty reduction. As a matter of fact, PFM reform is important to secure long-term economic success, to increase the transparency and accountability in country resource management, and create a better service delivery for citizens. Ivory Coast’s authorities are aware of this, after some years of economic crises in the 1980s and 1990s and a diagnosis of its public finance management system in 1999 which highlighted some dysfunctions, have started a huge public finance management reforms. The study has revealed that these reforms have helped to achieve such a unified budget and implement the Public Finance Management Information System (SIGFiP). Despite the political and military crisis that began in 2002 and lasted ten years, the implementation of these reforms has prevented the deterioration of fiscal indicators. There is evidence that without these reforms, the situation of public finances would worsen further.